The role of autoantibodies in the early diagnosis of systemic immunoinflammatory rheumatic diseases - L. P. Ananyeva (Современная ревматология)
The majority of systemic immunoinflammatory rheumatic diseases (SARDs — systemic autoimmune rheumatic diseases) have several stages. The most important characteristic of SARDs is pathological activation of B cells and overproduction of organ-specific autoantibodies (auto-Abs), which react with different peptides and cell components and are regarded as biological markers of rheumatic diseases. The main serological markers of SARDs include antinuclear antibodies, rheumatoid factors, anticyclic citrullinatedpeptide antibodies, antiphospholipid antibodies, and antineutrophil cytoplasmic antibodies. Positive tests for these auto-Abs are among the classification criteria for SARDs and are used to evaluate the activity and severity of the diseases, to identify some clinical laboratory subtypes, to predict the development and progression of organ pathology, therapy effectiveness, etc. Moreover, they may serve as predictors of SARD development at a preclinical stage. It has been proved that immunopathological disturbances associated with the loss of immune tolerance to self-antigens and with the initiation of systemic autoimmunity and inflammation develop 5 years on average before the appearance of the first clinical symptoms. Thus, detection of serological markers for SARDs at a preclinical stage, i.e. in the absence of extensive clinical manifestations, makes it possible to use preventive strategies in people at high risk for these diseases.Using rheumatoid arthritis, systemic lupus erythematosus, and systemic sclerosis as an example, the paper analyzes the clinical significance of detection of auto-Abs at preclinical or early clinical stages of SARDs when immunopathological disorders have not yet become severe and/or irreversible.